Studies Of Various Strains Of Echinococcus Granulosus In Livestock In Libya: Prevlence, Ultra-Structure, And Genotypes Of Hydatid Cysts. - Layla, Omran Elmajdoub (2013)
Hydatidosis of livestock is a widespread parasitic infection; Libya is not an exception. A total number of 32,971 livestock from different regions in Libya was examined for the prevalence rate. Morphological and molecular characterizations of E. granulosus isolates were also examined. the total prevalence rate in all study areas was 10.97%: 19.2% from sheep, 12.5% in the camels and 10.6% from cattle. The seasonal variations in the prevalence rates were almost similar in all three animals. Typically, the infection rates of hydatid cysts increased with age. Livers and lungs were the most commonly infected organs (43.1% and 42.1% respectively). The viability rates of fertile hydatid cysts in sheep and camels were 76.1% and 75.2% respectively with significant differences (P≤ 001) between them. The largest cyst size was found in the liver of camels (12.4 cm). The large and small hooks of protoscoleces were measured for their total, blade, and handle lengths as well as the width. From sheep, significant differences (P ≤ 0.01) between total lengths from different organs were seen. But based on the Discriminant Function Analysis (DFA), the differentiation in the liver and lung was low, but some lengths on spleen and mesentery with slightly high differentiation. For camels, significant differences (P ≤ 0.01) were seen between different organs. based on the DFA. The differences in the liver and lung were strong, but in the spleen it was low with most of them were distributed in the lungs. Tiny hooks were seen, denoting a possible presence of complete or incomplete third rostellar hooks.